El estado colombiano y el buen vivir : Un proyecto político educativo (2012)
This investigation (research) linked to the program of the Doctorate in Sciences of the Education of the Universidad del Cauca, Colombia, takes the GOOD LIVE as aim (lens) and backbone TO LIVE, Contemplating the life and the captivation for living, living in his condition to be human being and the recognition of the relation land - man in all this context. The education must be a way or as he, describes (Paulo Freire: 1965) The instrument in order that the man recovers his freedom and realizes changes, the recognition of the human thing. One proposes a political analysis of the historical condition of the human being in the last ten years or the last three governments of Colombia.